Wilayah Segregasi Etnik di Kota Medan - Sri Kunarsih; Tampilen Tampilen (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The purpose of this study is to describe the area of ethnic segregation in the city of Medan. Ethnic segregation is a concentration area where ethnic groups live based on similar backgrounds. This paper uses descriptive qualitative research methods with a case study approach. Data collection through literature study methods, interviews, and participatory observations. In the city of Medan although many ethnicities mingle but in terms of the area of residence still tend to be compartmentalized in similar ethnic concentration areas. In the concept of a plural and plural city system such as Medan such ethnic living conditions are considered less conducive. It should be in the plural and plural urban layout of each ethnicity that exists mingled by not expressing the symbols and background of the ethnicity. Thus creating a truly plural and plural social system in a complex social system.